Profiles of paediatric patients experiencing stroke-like episodes associated with mitochondrial disease - Molla, Gülhan Karakaya; Uzun, Özlem Ünal; Agakisili, Hanım Babazade; Genç, Emine; Gülten, Zümrüt Arslan; Yıldırım, Tarık; Ersoy, Aydan Sezgin; Ak, Belkıs; Gülbahçe, Aliye; Yıldız, Sevil; Çakar, Nafiye Emel; Karaca, Meryem; et al. (Frontiers in Neurology, 2025)
IntroductionStroke-like episodes (SLE) are defined as events characterized by the sudden onset of neurological symptoms with clinical manifestations similar to those of a stroke. However, they are distinguished by the presence of radiological lesions that do not conform to single vascular territory. MELAS syndrome, which is characterized by metabolic encephalopathy, lactic acidosis, and SLE, has been identified as the first genetically defined and most widely known mitochondrial cause of SLE. It has been demonstrated that SLE may occur in the course of a variety of mitochondrial diseases, including those that are the result of nuclear DNA mutations.ObjectiveIn this retrospective, multicenter, observational cohort study, we sought to determine the clinical, radiological, EEG, and genetic characteristics of patients with mitochondrial gene mutations presenting with SLE and the frequency and treatment of SLE.MethodsThirty-four patients with a genetically diagnosed mitochondrial disease from 9 paediatric metabolic disease centres in the Marmara Region of Turkey were included in the study, of whom 13 pateints had SLEs. Demographic characteristics, symptoms, clinical features, cranial MRI, EEG findings, and genetic characteristics were evaluated.ConclusionIn this study, stroke-like episodes in genetically defined mitochondrial disorders were most frequently observed in MELAS and POLG mutations, and rarely in CoQ10 deficiency, Leigh syndrome cases. Cranial MRI findings are often frontotemporal in location and inconsistent with vascular distribution, and focal epileptiform activity on EEG are diagnostically significant. In MELAS, clinical improvement was observed in patients when L-arginine was initiated in the acute period. The findings emphasise that SLE should be evaluated in the differential diagnosis of sudden onset neurological symptoms in mitochondrial diseases.